BUDAYA GAMO SOHO BAGI MASYARAKAT DI SUKU NGALIK DISTRIK SILIMO KABUPATEN YAHUKIMO - Yoel Giban (IAKN Ambon, 2020)
In general, tradition is born from a community habit that is continuously carried out which shapes the people's way of life. These habits have become a pattern of life and are made as an inheritance from our ancestors so that they are preserved and maintained as their shapes and patterns are adjusted to the times, even though the patterns are maintained as original as possible over time. Thus, the oral tradition as the nation's cultural wealth is one of the valuable forms of regional cultural expression, because it does not only store the cultural values ??of a traditional society, but also becomes the cultural root of a new society. So on that basis the oral tradition is able to record and document all events and incidents in oral form and become a narrative history as an oral cultural heritage. Likewise, “the various expressions of society that are expressed in the oral tradition do not only contain fairy tales, mythology, or legends as they are generally interpreted, but also concerning the cognitive system of society, sources of identity, means of expression, religious and belief systems, formation and enforcement of customs. Customs, history, law, medicine, beauty, creativity, community origins, and local wisdom regarding ecology and the environment. is teaching that has the character of advice or teaching and stays different from the word 'gomo which only has a single meaning, namely advice while it is associated with the word' gomo wene which means teaching about advice. Therefore, 'gomo wene' is part of the continuous teaching carried out by parents to the younger generation, especially to boys as the heir to the values ??of cultural traditions orally.